Characterisation of beta globin gene cluster deletions using multiplex-Gap-PCR and Multiplex Ligation-dependent Probe Amplification (MLPA) - Redzuwan, Yasmin Mohamad (2018)
Deletions in the beta (β)-globin gene cluster are usually rare, yet this type of mutation is problematic to detect, and subsequently possess a challenge in the diagnostic laboratory. Deletions in this cluster are usually related to the heterozygous of the delta beta thalassaemia (δβ-thalassaemia), hereditary persistence of foetal haemoglobin (HPFH) and some of the haemoglobin variants. These disorders are typically presented by elevated levels of haemoglobin F (Hb F), but with normal haemoglobin A2 (Hb A2). However, there is still limited number of studies focusing on this topic that has been carried out in Malaysia. As such this study was carried out to fill this knowledge gap. In this study, screening of the selected deletional mutations in the β-globin gene cluster among patients with high Hb F (>1%) and normal Hb A2 (<4%) was performed using a multiplex Gap-PCR and multiplex ligation-dependent probe amplification (MLPA). The results showed that no deletions were detected from all 24 patients when subjected to the multiplex Gap-PCR tested against four target deletions; delta beta (δβ) thalassaemia, hereditary persistence of foetal haemaglobin 6 (HPFH-6), Siriraj I and Hb Lepore. However, findings from the MLPA screening on 12 randomly selected samples revealed one patient was positive with double deletions within the region of the β-globin gene cluster. These deletions occur at gamma-globin gene 1 (HBG1) and gamma-globin gene 2 (HBG2) in exon 3. In tandem, this study also attempted to establish any correlations of the deletions detected with the haemotological profile presented by these patients. In conclusion, this study highlighted the importance of these deletion characterisations using multiplex Gap-PCR and MLPA, which helps in establishing a definitive diagnosis among the selected group of patients. Abbreviation: δβ-thalassaemia - delta beta thalassaemia; HPFH - hereditary persistence of foetal haemoglobin; Hb F - haemoglobin F; Hb A2 - haemoglobin A2; MLPA - multiplex ligation-dependant probe amplification; HBG1 - gamma globin gene 1; HBG2 – gamma globin gene 2